Enhancing Employee Performance: The Impact of Compensation, Motivation, and Work Ethic: Meningkatkan Kinerja Karyawan: Dampak Kompensasi, Motivasi, dan Etika Kerja - Junio, Evan Agung; Sumartik (Indonesian Journal of Law and Economics Review, 2023)
This study investigates the influence of compensation, motivation, and work morale on employee performance within the Marketing Distribution Department of a prominent organization. Employing quantitative methods and a sample of 101 respondents, data was collected through validated and reliable questionnaires. The analysis, conducted using classical assumption tests and multiple linear regression, reveals that compensation and motivation individually exert a positive and significant impact on employee performance, while work morale exhibits a positive but non-significant effect. Furthermore, when considered together, compensation, motivation, and work morale collectively have a positive and significant influence on employee performance. These findings underscore the importance of holistic approaches to employee engagement and provide valuable insights for organizations seeking to enhance their workforce's productivity and effectiveness. Highlights: Compensation and motivation positively impact performance. Work morale, while positive, lacks significant individual influence. Combined effects of compensation, motivation, and morale on performance are substantial. Keywords: Compensation, Motivation, Work Morale, Employee Performance, Quantitative Analysis